Social Representations of the Past and Transitional Justice in Latin America [Representações Sociais Do Passado E Justiça Transicional Na América Latina] [Representaciones Sociales del Pasado y Rituals de Justicia Transicional en América Latina] - Bilbao-Ramirez, M (Fundacao Carlos Chagas, 2015)
This article analyzed 5 surveys conducted in Latin American countries (N = 4900) regarding how people perceive and cope with collective violence during dictatorship periods. There is general agreement on the need to remember the past, where victims of collective violence and the left-wing showed a more positive attitude, reporting the necessity of sharing the facts and having a more positive evaluation of measures of transitional justice. Even when official apologies show a critical perception, a positive view of them is associated with a better perception of the emotional climate. While the sincerity and perceived effectiveness of apologies are higher among victims and the left-wing in Argentina and Paraguay, in Chile the opposite is true. Results are discussed in the framework of social representations of the past. © 2015, Fundacao Carlos Chagas. All rights reserved.